Exchange Rate Misalignments and Crises - Jerome L. Stein; Giovanna Paladino (Center for Economic Studies and ifo Institute (CESifo), 1999)
The problem is to evaluate the likelihood that a country will face a currency or balance of payments crisis over a given horizon. When is it rational for market participants to expect a depreciation of the currency? On the basis of considerable empirical studies we know that in both banking and currency crises, there is a multitude of weak and deteriorating economic fundamentals. Our theme is that there is an economic logic to medium and longer-term m ovements in exchange rates, within the context of a consistent dynamic stock-flow model. The equilibrium real exchange rate is a trajectory, not a point. We provide objective measures of the real fundamentals that determine the moving equilibrium real ex c hange rate, and explain the dynamic economic mechanism whereby the actual exchange rate converges to this moving equilibrium exchange rate, called the NATREX. The fundamentals are primarily social consumption/GDP, which is generally driven by fiscal polic y, and the productivity of the economy. Trends in social consumption/GDP, and in fiscal policy, reflected political regime changes in France, Germany and Italy.
Keywords: 330